Role of Fracture Mechanics in Failure Analysis. (2018) - Manoj Reddy, G.; Arunkumar, S.; Harikrishnan, R.; Nair, Sreehari P.
Abstract: Failure analysis is a serious procedure in determining the source of the problem. An important aspect in failure analysis is that, one must have an unbiased and open mind while assessing the evidence with a view to isolate the primary reason for failure. To accomplish this, failure analysis invokes many fields of engineering. Of all fracture mechanics is one of the best technology used for predicting and preventing the failure. In this article, the role of fracture mechanics in failure analysis is discussed. In this connection, the questions that fracture mechanics can answer in finding the root cause of the failure is substantiated with 13 case studies. After briefly introducing the subject, fracture mechanics, its approaches and associated fracture parameters are discussed. This would provide necessary background for the reader in appreciating the role of fracture mechanics in examining the failure